2013
DOI: 10.1007/s00432-013-1567-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and efficacy of different chemotherapeutic regimens in patients with mediastinal nonseminomatous germ cell tumors

Abstract: CPOB and TBEP regimen were significantly associated with better outcome in pts with MNGCT. Age ≥ 24 years and size of the primary mediastinal tumor ≥ 19 cm were found as independent negative prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Primary malignant MGCT constitutes 10% of the total GCTs treated at our center and identical to the incidence of 3%‐15% in published literature 1,4,6,16,19,21‐29 . Diagnosis is sometimes difficult in comparison to their gonadal counterpart due to differential diagnosis of thymic neoplasm, lymphoma, sarcoma, and other mediastinal lesions.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Primary malignant MGCT constitutes 10% of the total GCTs treated at our center and identical to the incidence of 3%‐15% in published literature 1,4,6,16,19,21‐29 . Diagnosis is sometimes difficult in comparison to their gonadal counterpart due to differential diagnosis of thymic neoplasm, lymphoma, sarcoma, and other mediastinal lesions.…”
Section: Discussionsupporting
confidence: 61%
“…Primary malignant MGCT constitutes 10% of the total GCTs treated at our center and identical to the incidence of 3%-15% in published literature. 1,4,6,16,19,[21][22][23][24][25][26][27][28][29] Diagnosis is sometimes difficult in comparison to their gonadal counterpart due to differential diagnosis of thymic neoplasm, lymphoma, sarcoma, and other mediastinal lesions. Mediastinal NSGCT is more aggressive in presentation with a high volume of disease in the majority of cases and superior vena cava obstruction may present in around 10% of cases but it was much higher (28%) in our series (Table 1) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this was the fourth largest single-center study of PMMGCTs to date, following reports from Russia, 17 China, 18 and Peru. 19 We reported more cases with advanced-stage PMMGCTs.…”
Section: Discussionmentioning
confidence: 96%
“…In a multicenter study that enrolled 341 patients with PMGCTs from USA and Europe, Bokemeyer et al ( 2 , 4 ) reported the 5-year OS and PFS rates for mediastinal nonseminoma were 45 and 44%, respectively. A more recent study showed the 5-year OS rate was 46% for nonseminomatous patients ( 21 ). In the oriental population, Wang et al ( 22 ) reported that the 5-year OS and PFS rates of mediastinal nonseminomatous patients were 49.2 and 32.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%